Brain networks underlying conscious tactile perception of textures as revealed using the velvet hand illusion - Rajaei, Nader (Hum Brain Mapp, 2018)
Humans are adept at perceiving textures through touch. Previous neuroimaging studies have identified a distributed network of brain regions involved in the tactile perception of texture. However, it remains unclear how nodes in this network contribute to the tactile awareness of texture. To examine the hypothesis that such awareness involves the interaction of the primary somatosensory cortex with higher order cortices, we conducted a functional magnetic resonance imaging (fMRI) study utilizing the velvet hand illusion, in which an illusory velvet‐like surface is perceived between the hands. Healthy participants were subjected to a strong illusion, a weak illusion, and tactile perception of real velvet. The strong illusion induced greater activation in the primary somatosensory cortex (S1) than the weak illusion, and increases in such activation were positively correlated with the strength of the illusion. Furthermore, both actual and illusory perception of velvet induced common activation in S1. Psychophysiological interaction (PPI) analysis revealed that the strength of the illusion modulated the functional connectivity of S1 with each of the following regions: the parietal operculum, superior parietal lobule, precentral gyrus, insula, and cerebellum. The present results indicate that S1 is associated with the conscious tactile perception of textures, which may be achieved via interactions with higher order somatosensory areas.